2008
DOI: 10.1176/jnp.2008.20.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Diagnostic Features of Delayed Hypoxic Leukoencephalopathy

Abstract: Delayed hypoxic leukoencephalopathy is an underrecognized syndrome of delayed demyelination, which is important to consider when delayed onset of neuropsychiatric symptoms follows a hypoxic event. The authors describe clinical and diagnostic features of three such cases, review the pathophysiology of delayed hypoxic leukoencephalopathy, and discuss features which may help distinguish it from toxic leukoencephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 18 publications
1
15
0
2
Order By: Relevance
“…The DPL and control cases did not have long TE spectra, however, the short TE spectrum suggest the presence of lactate in the DPL case (Figure 2A). This spectral pattern has been previously reported in the setting of DPL following carbon monoxide poisoning or medication overdose (10)(11)(12). Prolonged impaired oxygenation to the subcortical white matter is thought to promote anaerobic metabolism and leads to elevated tissue lactate (11,12).…”
Section: Case Seriessupporting
confidence: 68%
See 1 more Smart Citation
“…The DPL and control cases did not have long TE spectra, however, the short TE spectrum suggest the presence of lactate in the DPL case (Figure 2A). This spectral pattern has been previously reported in the setting of DPL following carbon monoxide poisoning or medication overdose (10)(11)(12). Prolonged impaired oxygenation to the subcortical white matter is thought to promote anaerobic metabolism and leads to elevated tissue lactate (11,12).…”
Section: Case Seriessupporting
confidence: 68%
“…This spectral pattern has been previously reported in the setting of DPL following carbon monoxide poisoning or medication overdose(1012). Prolonged impaired oxygenation to the subcortical white matter is thought to promote anaerobic metabolism and leads to elevated tissue lactate(11, 12).…”
Section: Discussionmentioning
confidence: 99%
“…(3,7) Pathologically, it is characterised by diffuse hemispheric demyelination sparing the subcortical U-fibres, but without vacuolisation. (8) Rizzuto et al reported a case of intravenous heroin abuse in which the clinical picture was consistent with post-anoxic encephalopathy, but a pathological study suggested spongiform leucoencephalopathy. (9) MR imaging findings were also consistent with TLE.…”
Section: Discussionmentioning
confidence: 99%
“…This spectral pattern has been previously reported in the setting of DPL following carbon monoxide poisoning or medication overdose. [13][14][15] Prolonged impaired oxygenation to the subcortical white matter is thought to promote anaerobic metabolism and leads to elevated tissue Lactate. 14,15 The observed increase of Cho/Cr ratios in the patients with leukoencephalopathy, particularly in the case of COVID-associated necrotizing leukoencephalopathy, likely reflects demyelination within these white matter lesions as recently described in an initial neuropathologic study of a patient with COVID-19.…”
Section: Discussionmentioning
confidence: 99%